Curriculum Integration: An Experience in the First Year of the Two-year Program Conducive to a Licenciatura in Pedagogy with a Specialization in Preschool Education - Ana Lucía Chaves-Álvarez; Dora María Hernández-Vargas; Jorge León-Sánchez; Zulay Pereira-Pérez; Marie Claire Vargas-Dengo (Universidad Nacional, Costa Rica, 2011)
This paper is a reflection on the curriculum integration experience of faculty members in the first year of the two-year program conducive to a Licenciatura(*) in Pedagogy with a specialization in Preschool Education of the Division of Basic Education, Universidad Nacional, Costa Rica, during the first half of 2011. The integration has been designed by the faculty members as a process of personal and professional growth, which will help to generate opportunities for team building, student development and integration of courses.   (*) Translator's Note: "Licenciatura" or "Licentiate's Degree" is a two year post-graduate study program, usually including thesis.